The Role of the International Environmental Cooperation in Achieving Sustainable Peacebuilding in International Relations: A Comprehensive and Critical Analysis - Albakjaji, Mohamad; Khammassi, Soumaya; Alshanqityi, Yusra (Journal of Posthumanism, 2025)
Despite scientific and technological advancements, the international community faces a dual challenge: maintaining global peace while addressing accelerating environmental degradation. Environmental issues such as climate change, desertification, biodiversity loss, and water scarcity have increasingly become catalysts for conflict, particularly in regions characterized by socio-economic vulnerability, political instability, and weak institutional frameworks. In response, "global environmental peacebuilding" has emerged as a framework that not only seeks to protect the environment but also aims to mitigate conflict through cooperative natural resource management. This research investigates the evolution of international environmental peace and its significance within international relations. It critically examines theoretical foundations of environmental cooperation, analyzes multilateral legal frameworks, assesses empirical case studies, and explores challenges and limitations of this emerging paradigm. The central argument is that environmental governance—when embedded within robust international institutions and complemented by comprehensive domestic policy frameworks—can serve as a powerful mechanism for sustaining peace and preventing conflict, especially when initiatives address power asymmetries, engage local communities, and establish effective monitoring mechanisms.